Highly active and durable MNS bifunctional electrocatalysts for enhanced anion exchange membrane water electrolysis - Singh, Kailash; Yadav, Himanshu; Samdani, Kunda; Selvaraj, Kaliaperumal (Electrochimica Acta, 2025)
The development of non-platinum group metal (non-PGM) electrocatalysts with performance comparable to their noble metal counterparts remains a significant challenge for overall water splitting. In this study, we demonstrate the performance of an Anion Exchange Membrane (AEM) water electrolyzer using a bifunctional, non-PGM electrocatalyst: reduced graphene oxide (rGO)-encapsulated MoS2/Ni3S2 (MNS) grown on a nickel foam (NF) substrate. The rGO/MoS2/Ni3S2 (rGO-MNS) electrode was synthesized via a facile, single-step hydrothermal method. For the hydrogen evolution reaction (HER), the rGO-MNS electrode exhibited a low overpotential of 94 mV at a current density of 100 mA cm-2, maintaining excellent stability over 50 h with a minimal degradation rate of 120 mu V h-1. In the case of the oxygen evolution reaction (OER), an overpotential of 410 mV was required to reach the same current density, with a similarly robust durability and a degradation rate of only 360 mu V h-1. When employed as symmetric electrodes for overall water electrolysis, the rGO-MNS system achieved a current density of 10 mA cm-2 at a cell voltage of 1.51 V, outperforming the benchmark Pt/C & Vert;Ru/C catalyst pair, which required 1.58 V to reach the same performance. The enhanced electrocatalytic activity and durability are attributed to the conductive rGO encapsulation, which facilitates charge transfer and mitigates surface oxidation of the catalyst. These results present a promising strategy for designing cost-effective, durable, and highperformance non-PGM electrodes for AEM water electrolysis.
Keywords: Anion Exchange Membrane Water Electrolysis; Bifunctional Electrocatalyst; hydrogen evolution reaction; Oxygen Evolution Reaction; rGO-MNS